Caracterización química y efecto antinflamatorio del extracto metanólico de las hojas de Pelargonium robertianum L. «geranio», en Mus musculus - Ibáñez V., Lucy A. (2003)
The purpose of the present investigation has been to evalue DL50 and effective dose average DE50 of antiinflamatory effect of the methanolic extract of the leavs of Pelargonium robertianum L «Geranio». To evaluate the DL50, 36 mice were used and divided in groups of 6 animals; administe doses different from the methanolic extract by oral route by means of intragastric cannulas, observed constantly during the firts 24, 48 and 72 hours. The value of the DL50 was of 8,717.0 mg/kg by Lichfield and Wilcoxon Method. Also to evaluate the DE50, following Winter and Sughisita technique, 50 male albine rats.The weight average ranged between 200 to 250g. and were divided randomly in 5 groups of experimentation:I G, Negative Control (Distilled Water, 3 ml/kg) II G, Positive control (Diclofenac, 10 mg/kg); III, IV and V Groups were given 250, 500 y 1000 rng/kg respectively. The administration was made by oral route 30 min before the subplantar injection of 0,1 mililiter of 1 % carragenan in the posterior right leg and in the opposite leg an equal volume of 0.9% satine solutíon. Observing that the methanolic extract presented an inhibitory effect in comparison to inflammation presented by Diclofenac (62%) obtaining fue 26;38 and 57% far the different doses and the Average Effective Dose has been of 681,9577 by the metllod of Probist and ANOVA (p=O.OOOI, F-5240, R2=O.9979). In tIle bioactive extrael finding the following were found phenolics as compounds flavonoids: Rutín and Quercetin, inhibitors of the ciclooxigens observed by HPLC y TLC respectively and alkaloids named: GM1, GM2, GM3, has been analyzed by means of IR, HPLC, RMNCI3, RMNHI.